Atención y memoria en pacientes con consumo de marihuana del Centro de Salud ESPOCH – LIZARZABURU. Riobamba, 2020 - Esmeraldas Quiñónez, Steven Mauricio (2021)
The main objective of the present study was to analyze the attention and memory rates of patients who consume marijuana at the Intensive Outpatient Unit of the ESPOCH Type C Health Center - Lizarzaburu with a sample of 30 medical records, the methodology used was documental, bibliographic, non-experimental cross-sectional design and of a descriptive level. The technique used was the observation, an observation file was prepared, and it recorded important sociodemographic data and also the results of the accomplishment of the Neuropsi Neuropsychological Battery Attention and Memory previously applied by psychologists in charge of the Intensive Outpatient Clinic of the Health Center. Among the results with the greatest impact, it was found that in the average of subtests, memory curve and logical memory subtests of short-term memory with 6.85 and 6.66 respectively; pairs associated with 7.57 and long-term logical memory with an average of 7.57 and 5.79 correspondingly, which are related to an impairment. Consequently, to the percentage obtained that relate an alteration to the consumption of marijuana, neuropsychological rehabilitation strategies focused on memory were developed, which may be put to consideration for application by the mental health professionals of the health center.